CyberKnife Stereotactic Radiosurgery for Spinal Haemangioblastoma: A Single Centre Experience. (1st October 2022) - Palmer, Kieran; Whitelaw, Gemma; Krishnan, Anant; Dean, Chris; De Luna, Paolo Jose; Mitchell, Adam; Plowman, Nick; Lewis, Rachel
Abstract: AIMS: 'CyberKnife' stereotactic radiosurgery (SRS) is increasingly being used as a treatment for spinal haemangioblastoma to avoid complex surgery, especially in patients with multi-focal tumours associated with von Hippel-Lindau syndrome (VHL). Here we present the outcomes of patients treated in our centre. METHOD: Retrospective review of patients treated at St Bartholomew's Hospital, London. Assessment of radiological response was based upon RECIST criteria. The development of a symptomatic new or worsening cyst was included in the definition of progression when determining overall tumour control. Solid and overall tumour control rates were calculated using the Kaplan-Meier method. RESULTS: 14 tumours in 10 patients were included. 70% of patients were male and 90% had VHL. 9 (64%) tumours had an associated cyst. The median (IQR) age at treatment was 45.5 (43.5 – 53). The median gross tumour volume was 0.355cc. Patients received a mean marginal prescribed dose of 9.6Gy in a single fraction (mean central dose 14Gy) – dose constrained by spinal cord tolerance. Mean follow up was 15.4 months. 7 patients' symptoms improved or were stable and 3 worsened. Radiologically, 11 (78.6%) of tumours were stable or regressed, and 3 (21.4%) progressed. The 1-year solid tumour and overall tumour control rates were 92.3% and 75.7% respectively. All patients were alive at most recent follow up. 2 patients developed grade 1 adverse related events. CONCLUSION: SRS is a safe and effective treatment modality for spinal haemangioblastoma. Further prospective randomised trials with longer follow up are required to determine the optimum management strategy.